Insights into the expanding phenotypic spectrum of inherited disorders of biogenic amines - Kuseyri Hübschmann, Oya; Horvath, Gabriella; Cortès-Saladelafont, Elisenda; Yıldız, Yılmaz; Pons, Roser; Friedman, Jennifer; Mercimek-Andrews, Saadet; Wong, Suet-Na; Pearson, Toni S.; Zafeiriou, Dimitrios I.; Kulhánek, Jan; Kurian, Manju A.; et al. (Nature Communications, 2021)
Abstract - Inherited disorders of neurotransmitter metabolism are rare neurodevelopmental diseases presenting with movement disorders and global developmental delay. This study presents the results of the first standardized deep phenotyping approach and describes the clinical and biochemical presentation at disease onset as well as diagnostic approaches of 275 patients from the registry of the International Working Group on Neurotransmitter related Disorders. The results reveal an increased rate of prematurity, a high risk for being small for gestational age and for congenital microcephaly in some disorders. Age at diagnosis and the diagnostic delay are influenced by the diagnostic methods applied and by disease-specific symptoms. The timepoint of investigation was also a significant factor: delay to diagnosis has decreased in recent years, possibly due to novel diagnostic approaches or raised awareness. Although each disorder has a specific biochemical pattern, we observed confounding exceptions to the rule. The data provide comprehensive insights into the phenotypic spectrum of neurotransmitter disorders.
Gesehen am 21.04.2022